Strike a happy medium: the effect of it knowledge on venture capitalists' overconfidence in it investments - Singh, Harpreet (2021)
In this article, the effect of IT knowledge on the overconfidence of venture capitalists (VCs) in their IT investments is examined. Our findings show that the effect of IT knowledge on overconfidence is nonlinear. VCs with moderate levels of IT knowledge are least overconfident. At the same time, VCs with moderate levels of IT knowledge are most resistant to the biasing effects of past successes. Past failures show a negative association with overconfidence independent of the level of the VC's IT knowledge. Finally, the negative association between stakes and VC overconfidence is stronger with greater levels of IT knowledge. These results shed light on the highly disputed role of IT knowledge in the domain of IT investments.